Esophageal Rupture Due to Diving in Shallow Waters - Sung Ho Han; Soon-Ho Chon; Jong Hyun Lee; Min Koo Lee; Oh Sang Kwon; Kyoung Hwan Kim; Jung Suk Kim; Ho hyoung Lee; June Raphael Chon (Journal of Trauma and Injury)
Delayed esophageal rupture due to blunt injury is not new. However, rupture due to suspected barotrauma is very rare. We describe a case of esophageal rupture in a male 24-year-old patient after diving in shallow waters. The patient was quadriplegic and could not experience the typical chest pain related to rupture and resulting mediastinitis. The rupture was discovered 4 days after emergency decompressive laminectomy and fusion for his cervical spine. The rupture was evidently caused by barotrauma and was discovered four days after admission. He underwent primary closure and pericardial flap as a life-saving procedure.